A Model for Development Planning Process Based on the Sustainable Development Approach in the Iranian Oil Industry - Zahra Banasadegh; Shamssosadat Zahedi; Gholamali Gholamali Farjadi (فرایند مدیریت و توسعه, 2020)
The complexity and extent of sustainable development concept calls for the capability to apply planning tools to introduce optimal relationship among all aspects of development and to materialize all principles of sustainability. Related literature and sustainable development processes in some countries, as well as 30 companies affiliated to the Iranian Oil Industry, which were all practicing sustainable development approach, were studied to reach a model for sustainable development. Results show that the outcomes of the six main steps or processes (starting with the stage of planning, stakeholders’ participation, preparing planning draft, formulating the vision, preparing outcomes framework, and planning for implementation), as well as fourteen secondary steps and processes (creating the core of planning, preparing the schedule, preparing instructions, assigning planning stakeholders, identifying problems on the basis of geographical regions, identifying problems related to sustainable development, assigning sustainable development stakeholders, identifying problem solving resources, formulating the vision, setting objectives, determining outcomes, formulating indexes, determining implementation resources, and designating responsibilities) are at a favorable level. However, only the two secondary processes of formulating indexes and designating administrative responsibilities need improvement.